Dampak Media Sosial Tiktok Terhadap Gaya Bahasa Anak Usia Sekolah Dasar (Indo-MathEdu Intellectuals Journal, 2025)
TikTok is a platform that is very popular among children, especially elementary school children. The aim of the research is to understand the extent of TikTok's influence on the language styles of elementary school aged children. This research uses a library research method with a qualitative approach to analyze relevant documents and literature. The data analysis used is interactive data analysis by sorting various information from various literary sources such as journal articles, books, related social media Tiktok and its influence on children's language styles. The results of this research show that the TikTok platform, which provides various forms of videos with expressive language, has an impact on children's language transition to informal language. The most striking language that appears among TikTok users is slang. Starting from the choice of words or diction used in TikTok trends such as "bestie", "slebew", "gabut", "mager", and "gaje", and combining foreign languages into Indonesian or what is called code mixing such as "OMG, it's really funny!", "I'll skip it first", "The vibes are really good", and "You're glowing even more".